Blanket-like Co(OH)2/CoOOH/Co3O4/Cu(OH)2 composites on Cu foam for hybrid supercapacitor. (20th February 2020) - Yu, Yawei; Wang, Haimei; Zhang, Haoze; Tan, Yurong; Wang, Yunlei; Song, Kefan; Yang, Bingqian; Yuan, Lefan; Shen, Xiaodong; Hu, Xiulan
Abstract: Novel blanket-like Co(OH)2 /CoOOH/Co3 O4 /Cu(OH)2 composites on Cu foam are prepared through the electrochemical conversion of the precursors synthesized using hydrothermal method, named as CV sample. After the electrochemical conversion, flatbread-like precursors changes to blanket-like Co(OH)2 /CoOOH/Co3 O4 /Cu(OH)2 consisting of many nanowires. The CV sample has a specific area of 228.4 m 2  g −1, which is obviously larger than 24.5 m 2  g −1 for the precursors. The CV sample has a specific capacity of 290.8 μAh cm −2 (1.94 F cm −2 ) at 1 mA cm −2 and a capacity retention of 80.9% after 10000 cycles at 64 mA cm −2 . A hybrid supercapacitor consisting of CV sample as a positive electrode and heated carbon cloth as a negative electrode has an areal capacity of 245.1 μAh cm −2 (0.552 F cm −2 ) at 2 mA cm −2, an energy density of 196.1 μW h cm −2 at 1.6 mW cm −2 . The initial phase conversion from the precursors to Co(OH)2 /CoOOH/Co3 O4 /Cu(OH)2 induced by alkaline electrolyte resulted in smaller charge transfer and ion diffusion resistance, larger surface area, more active sites and better structural compatibility, which were demonstrated to be the critical factors for the capacity enhancement.